Animals backbones: viva education: science works for kids series - Moore, Jo Ellen (Viva Education New Delhi, 2004)
This companion book focuses on vertebrates, featuring animals that have backbones, such as mammals, birds, reptiles, amphibians, and fish. It provides insights into their characteristics, behaviors, and habitats, using vibrant illustrations to captivate young readers. The book aims to foster an appreciation for the variety and complexity of vertebrate life.